Quality of Service on Satisfaction and its Impact on Patient Trust Levels - Daryanto; Sumardi; Andi Aswan (The Scientia Law and Economics Review, 2023)
In its declaration, there were various polemics related to the quality of hospital services after the implementation of the Health BPJS program. Some people think it will affect the quality of service. In creating good quality, many things are needed, one of which is how a company carries out quality control. It is important to carry out continuous quality control so that the products produced by the company are in accordance with the standards set by the company and in line with the standards set by the authorized agency. What is the relationship between tangible, responsiveness, reliability, assurance, and empathy on patient satisfaction? There are still few researchers who explore this question. This study aims to examine and analyze the effect of: a) tangible on patient satisfaction; b) responsiveness to patient satisfaction; c) reliability of patient satisfaction; d) assurance of patient satisfaction; e) empathy for patient satisfaction. This research was conducted at Inco Sorowako Hospital. The research method used is a descriptive survey method. Collecting data by distributing questionnaires to the respondents. The population in this study were all outpatients and inpatients at Inco Sorowako Hospital. The sample in this study is part of the population of outpatient and inpatient patients at Inco Sorowako Hospital for the period May-June 2017 which have relatively the same characteristics and are considered to represent a population of 100 people. The analysis technique uses Structural Equation Modeling analysis. The results of the analysis show that tangible, responsiveness, reliability, assurance, and empathy have a positive and significant effect on patient satisfaction. Service quality has a positive and significant effect on patient trust, and patient satisfaction has a positive and significant effect on patient trust.